Two new hosts for Caligus bonito Wilson C.B., 1905 (Copepoda, Siphonostomatoida, Caligidae) from Turkey. - Öktener, A., A. Alas & D. Türker (International Journal of Bonorowo Wetlands, 2017)
Two new hosts for Caligus bonito Wilson C.B., 1905 (Copepoda, Siphonostomatoida, Caligidae) from Turkey. Bonorowo Wetlands 7: 1-3. Caligus bonito Wilson C.B., 1905 (Copepoda, Siphonostomatoida, Caligidae) was reported for the first time on the gill filaments of Sarda sarda (Bloch, 1793), Auxis rochei (Risso, 1810) from Turkish marine waters. The morphological characters of this cosmopolitan parasitic copepod are given using photographs. This study presents two new host species and a new geographic distribution of Caligus bonito in Turkey.